Exploring the Students’ Perceptions of Entrepreneurship Courses at Indonesian Higher Education - Muhammad Nasir (Lembaga Penjaminan Mutu, IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2023)
Entrepreneurship education serves as an essential foundation within the mission of entrepreneurial universities. It plays a pivotal role in shaping students' mindsets and competencies. Achieving this objective also requires effective entrepreneurship teaching and curriculum design to align with the main goals of its implementation. The present study seeks to explore the overall students’ perceptions on the entrepreneurship courses. This is important to evaluate the course curriculum, delivery and other considerations to effectively facilitate students’ competencies, motivation and mindset to pursue entrepreneurship. Quantitative approach using survey method was employed to a small sample of 35 students (m=9, f=26) of undergraduate program of Management at Universitas Negeri Medan, Indonesia. The findings from the quantitative descriptive analysis reveal positive attitudes towards entrepreneurship courses, with students acknowledging their effectiveness in enhancing knowledge, fostering creativity and innovation, and increasing motivation towards entrepreneurship. This study recommends that entrepreneurship educators, instructional designers, and faculty members should carefully consider the selection of learning materials, teaching methods, and evaluation tasks. Additionally, facilitating or encouraging students to engage in extracurricular activities and providing counseling services are essential steps to involve students in practical, real-life entrepreneurial scenarios.